Polygamy in Indonesia: A Critical Interpretation through the Lens of Mubadalah Theory - Rohmadi Rohmadi (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2024)
Indonesia’s marriage legislation primarily endorses monogamy, limiting men to one wife in line with the mubadalah principle, which emphasizes justice. Despite this, polygamy remains common and is a significant factor in divorce cases within religious courts. This study investigates polygamy through the mubadalah perspective to achieve gender justice, utilizing qualitative research methods and a literature review to analyze traditional gender roles in Indonesia. The findings reveal a deep societal divide on polygamy. Supporters often cite religious justifications and historical practices, especially in rural and certain ethnic communities. In contrast, critics raise concerns about systemic injustices against women, including emotional and psychological harm, power imbalances, and reduced autonomy. They argue that polygamy undermines the principles of equality and mutual respect that should characterize marriage. The legal framework governing polygamy, established by the Marriage Law No. 1 of 1974 and the Compilation of Islamic Law, allows polygamy under strict conditions but fails to adequately address gender equality issues. Integrating mubadalah principles into this legal framework could lead to reforms prioritizing women’s rights and fostering equitable family dynamics. Ultimately, this study highlights the need for a nuanced dialogue on polygamy that respects cultural traditions while advocating for gender equality and justice. The principles of mubadalah offer a pathway to healthier family relationships and a more equitable legal framework